Break through prayer : the secret of receiving what you need from God - Cymbala, Jim, 1943- (Zondervan, 2003)
A practical and visionary approach to the principles of prayer that will revolutionize our lives---and enable us to receive all God has for us Many people are missing the great things God wants to do in their lives because they don't know how to receive answers to their prayers. This revolutionary book is not a step-by-step guide on how to pray but an inspiring vision that moves people to greater hope as they see the tremendous potential of prayer. Breakthrough Prayer is peppered with amazing stories of answered prayer from the Brooklyn Tabernacle, including the story of the final survivor of the World Trade Center collapse and the prayers she prayed before becoming the last person pulled from the wreckage alive. Unique features include: * Breakthrough to Holiness: What is the connection between how we live and how we pray? * Breakthrough to Power: What are the prayers that really have power with God? * Breakthrough to Listening: How can we learn to recognize God's answers to our prayers? Jesus said and did only the things he received from the Father. When we do the same, the real potential of our lives will unfold, and prayer will enable us to become people with instructed tongues who are able to sustain others in fearful times---times much like those we face today. 'Voices inside my head were constantly screaming at me. I became like an animal in the street, muttering or yelling out a stream of profanity as people passed by. One day, lying in a hospital bed, close to death, I cried out, Jesus, help me! O God, you're my only hope! That was the breakthrough prayer that saved my life.' --Danny 'Talk about breakthrough prayer! I was buried under 110 stories of steel and concrete on 9/11. But God heard my prayer for a miracle.' --Genelle 'My husband and I had a dream of helping desperate young women. But no banker in his right mind would finance such a venture. So we prayed and God broke through every single obstacle we faced. That was just the beginning of the wonderful roller coaster ride we call 'faith'.' --Grace